The challenges of decarbonising heating of rural UK homes - Agzennai Soares, Samir (2025)
In UK law, the country must reduce it’s carbon emissions by 100% by 2050 in comparison to emissions produced in 1990 (UK Parliament 2008). Simply put the United Kingdom must reduce it’s emissions to net zero by 2050. Domestic heating currently accounts for the largest proportion of CO2 emissions of the UK, where effort has been made to decarbonise improve UK housing stock. The vast majority of which are in urban and suburban environments. The work in this thesis comprises of understanding the current state and challenges to decarbonise rural homes, particularly remote home heating. Enabling lower emissions homes and heating in rural settings is more challenging and costlier due to various factors such as remoteness, lack of infrastructure, government awareness and other factors. This work is seeking to contribute to awareness and understanding of rural domestic energy access and the challenges in reducing household energy emissions in this setting.